Artefatos em ferro de origem terrestre : um estudo de caso sobre a interface entre pesquisa arqueológica e conservação no sítio Charqueada Santa Bárbara, Pelotas, RS, Brasil - Vasconcelos, Mara Lúcia Carrett de (2014)
The current state of degradation of most archaeological collections has compromised the research and protection of this heritage. To respond to these problems, some initiatives that seek to modify the current practices of preservation of archaeological collections are emerging, as the fieldwork in the Charqueada Santa Barbara archaeological site ( Pelotas, RS, Brazil ), linked to the research project Pampa Negro: Arqueologia da Escravidão na Região Sul do Rio Grande do Sul (1780-1888), which has brought together a multidisciplinary team to talk about the praxis of each area and to think of appropriate solutions for the better management and protection of archaeological collections. In the context of the conservation, protocols for preventive and curative intervention of different types of materials were developed and tested in field and laboratory. Among the types of material recovered in the excavation, metal objects, especially iron, are those most susceptible to deterioration due to the process of recovery and to the speed at which the corrosive processes occur as well as the complexity of the products resulting from these. In this context, the aim of this study was to analyze, from a study of the interface between conservation and archeology, how the conservation procedures performed in the field and laboratory in the ferrous artifacts contributed to the preservation of archaeological collections. It was expected to verify which interventions enable a better conservation of archaeological origin and of the associated information material culture, and disseminate the need for greater integration between the experts related to the safeguard of the archaeological heritage areas. It was concluded that conservation practices directly assist in the preservation of archaeological collections in its material, documentary and symbolic aspects. Therefore, the conservator has become more of a manager of these collections, in a performance that, increasingly, is turning into an agent crucial to the management of the archaeological heritage.